Pluteus section Celluloderma (Pluteaceae): two new species in the Pluteus podospileus clade - Keerthi, V.; Justo, Alfredo; Ševčíková, Hana; Pradeep, C.k. (Phytotaxa, 2024)
Two new species (Pluteus parvulus and P. pauxillus) in the Pluteus podospileus clade are described based on morphological and molecular (nrITS) characters. Pluteus parvulus is characterized by small, thin, basidiomata with a brown pruinose pileus, pigmented lamella edges, polymorphic cheilocystidia and subglobose to broadly ellipsoid basidiospores. Pluteus pauxillus is distinguished by its small, brown pruinose pileus and stipe, dotted brown lamella edge, broadly ellipsoid to ellipsoid basidiospores, clavate, broadly clavate to fusiform cheilocystidia and abundant caulocystidia. Pluteus parvulus is found both in India and Korea, while P. pauxillus is so far known only from India.